50 Adjunctive Buprenorphine/Samidorphan Combination in Patients with Major Depressive Disorder: Phase 3 Long-term Extension Study Results. (12th March 2019) - Thase, Michael; Stanford, Arielle D.; Memisoglu, Asli; Martin, William; Claxton, Amy; Bodnik, J. Alexander; Trivedi, Madhukar H.; Fava, Maurizio; Pathak, Sanjeev
Abstract: Introduction: Buprenorphine/samidorphan (BUP/SAM), a combination of BUP (a µ-opioid receptor partial agonist and κ-antagonist) and SAM (a sublingually bioavailable µ-opioid antagonist), is an investigational opioid system modulator for depression. BUP/SAM has shown efficacy versus placebo as an adjunctive treatment for major depressive disorder (MDD) and a consistent safety profile in previously reported, placebo-controlled clinical studies. 1, 2 Study Objective(s): 1. To characterize the safety profile following long-term treatment with BUP/SAM 2. To explore depression symptoms and remission rates in patients with MDD following long-term treatment with BUP/SAM Methods: FORWARD-2 (Clinicaltrials.gov ID: NCT02141399) enrolled patients who had participated in 1 of 4 controlled studies as well as de novo patients. All patients had a confirmed diagnosis of MDD, had a history of inadequate response to standard antidepressant therapies (ADTs), and had been treated with an adequate dose of an established ADT for ≥8weeks before BUP/SAM initiation. ADT dosage could be titrated, but the ADT could not be changed. During the study, patients received open-label, sublingual BUP/SAM 2mg/2mg as adjunctive treatment for up to 52weeks. Safety (primary objective) was assessed via adverse events (AEs), vital signs, laboratory analytes, and electrocardiography. Suicidal ideation or behavior (SIB) was evaluated by the Columbia Suicide Severity Rating Scale. Abuse potential, dependence, and withdrawal were assessed by AEs and the Clinical Opiate Withdrawal Scale. Exploratory efficacy endpoints included mean Montgomery–Åsberg Depression Rating Scale (MADRS) scores and remission rate (MADRS ≤10). Results: Of 1454 total patients, 49% completed the 52-week study, 11% discontinued due to an AE, and 40% discontinued because of other reasons as of the interim data cutoff date (April 30, 2017). Most AEs were of mild/moderate severity. Serious AEs were reported in 3.2% of patients. AEs occurring in ≥10% of patients were nausea, headache, constipation, dizziness, and somnolence. There was no evidence of increased risk of SIB with BUP/SAM. Incidence of euphoria-related events was low (1.2%). After abrupt discontinuation of BUP/SAM, there was little evidence of withdrawal. BUP/SAM was not associated with meaningful changes in laboratory or metabolic parameters or in bodyweight. The mean MADRS score decreased from 22.9 (±9.7) at baseline to 9.8 (±8.8) after 52weeks. The remission rate at 52weeks was 52.5%. Conclusions: Long-term treatment with BUP/SAM did not reveal any new safety findings and confirmed that the risk of abuse and dependence with BUP/SAM was low. BUP/SAM maintained an antidepressant effect for up to 52weeks of treatment in patients with MDD. Funding Acknowledgements: Alkermes, Inc.